A novel chemical process of Bi2Te2.7Se0.3 nanocompound for effective adjustment in transport properties resulting in remarkable n-type thermoelectric performance. (1st July 2016) - Kim, Cham; Kim, Chang Eun; Baek, Ju Young; Kim, Dong Hwan; Kim, Jong Tae; Ahn, Ji Hyeon; Lopez, David Humberto; Kim, Hoyoung
Abstract: Chemical reaction processes for thermoelectric nanomaterials have received a lot of attention because of subsequent small and uniform nanostructures, causing a remarkable reduction in thermal conductivity; however, they typically showed low electrical properties possibly due to contaminations by chemicals resulting in low ZT. We devised a new chemical process for synthesizing an n-type Bi2 Te2.7 Se0.3 nanocompound without the chemicals causing potential contaminations. The product exhibited a predominant electrical conductivity while retaining the advantage of chemical reaction routes; thus, synergistic effect of the thermoelectric transport properties was greatly induced, resulting in the highest ZT among n-type Bi2 Te3 materials in bulk phase. Graphical abstract: